Synthesis, X-ray molecular structure, biological evaluation and molecular docking studies of some N4-benzyl substituted 5-nitroisatin-3-thiosemicarbazones. Issue 3 (1st February 2017) - Pervez, Humayun; Khan, Nazia; Zaib, Sumera; Yaqub, Muhammad; Naseer, Muhammad Moazzam; Tahir, Muhammad Nawaz; Iqbal, Jamshed
Graphical abstract: A possible binding mode of compound5g bound to active pocket of Jack bean urease. Abstract: A series of fifteen N 4 -benzyl substituted 5-nitroisatin-3-thiosemicarbazones5a –o was synthesized and evaluated for urease inhibitory, phytotoxic and cytotoxic influences. All the compounds proved to be highly potent inhibitors of the enzyme, showing inhibitory activity (IC50  = 0.87 ± 0.25–8.09 ± 0.23 μM) much better than the reference inhibitor, thiourea (IC50  = 22.3 ± 1.12 μM) and may thus act as persuasive leads for further studies. In phytotoxicity assay, twelve out of fifteen thiosemicarbazones tested i.e.5a –e, 5g, 5i and5k –o appeared to be active, exhibiting weak or non-significant (5–35%) growth inhibition at the highest tested concentrations (1000 or 500 μg/mL). In contrast, only one compound i.e.5i was active in the brine shrimp ( Artemia salina ) lethality bioassay, demonstrating cytotoxic activity with LD50 value 2.55 × 10 −5  M. Molecular docking studies of compounds5a –o were also performed to identify their probable binding modes in the active site of the enzyme.